Desenvolvimento, caracterização e estudo in vivo de imunolipossoma anti-EGFR para liberação de cabazitaxel em câncer de próstata - Sousa, Ana Carolina Cruz de (2024)
Prostate cancer or PCa is the fourth most common cancer in the world, the treatment of which may have limited effectiveness due to side effects and hypersensitivity. The application of nanocarriers, such as liposomes, functionalized with monoclonal antibodies is an innovative alternative in selective delivery to the tumor environment. In this sense, cetuximab, an anti- EGFR (Epidermal Growth Factor Receptor) monoclonal antibody, was used in the development of immunoliposomes encapsulated with cabazitaxel in order to minimize the cytotoxicity of the drug in non-tumor tissues, reducing side effects and improving delivery. of cabazitaxel selectively to the tumor for cells that overexpress EGFR. Liposomes were prepared by the lipid film hydration method testing the lipids Soy phosphatidylcholine (SPC), Hydrogenated soy L- α-phosphatidylcholine (HSPC), 1,2-distearoyl- sn -glycero-3-phosphocholine (DSPC), cholesterol and 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[amino(polyethylene glycol)-2000] (DSPE-PEG-2000) conjugated with cetuximab. The formulation that presented the best characterizations was based on the composition of SPC:Col:DSPE-PEG-2000 (20:2:1) and cabazitaxel (1:20), presenting a particle size of 95 ± 3.97 nm, polydispersity index of 0.270 ± 0.1 and zeta potential of -16.4 ± 1.18 mV. The immunoliposomes showed a high percentage of cabazitaxel encapsulation, 89 ± 9.8%, and a conjugation efficiency percentage of 39%. Electronic microscopy revealed the spherical shape of the formulations. Thermophoresis showed the presence of cetuximab in the immunoliposomes without altering the structure and integrity of the antibody. Assessment of antibody interaction by ELISA showed that immunoliposome formulations interacted with the EGFR receptor. Cell uptake and viability assays showed that despite the internalization of the formulations in non-tumor cell lines, it did not result in cytotoxicity. The evaluation of tumor inhibition in vivo showed that immunoliposomes caused greater regression of tumor volume, with greater animal survival. Systemic toxicity analysis revealed a leukopenia effect, related to cabazitaxel and already described in the clinic, while histological analysis revealed no obvious toxicity. Therefore, the immunoliposomes developed presented appropriate physicochemical characterizations, without cytotoxic activity for non-tumor cell lines, and which resulted in significant tumor regression in an in vivo model with increased mouse survival, possibly by targeting the EGFR ligand.